ANALISIS PEMANFAATAN DANA DESA UNTUK PENINGKATAN PENDAPATAN MASYARAKAT DESA SARI GALUH KECAMATAN TAPUNG KABUPATEN KAMPAR - Ilham, Akhary; Hendro, Ekwarso; Dahlan, Tampubolon (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This study aims to determine the impact of the use of Village Funds for Increasing the Income of Sari Galuh Village, Tapung District, Kampar Regency. The research population is the entire community in Sari Galuh Village, which is the head of the family in Sari Galuh Village who are involved in the Village Fund utilization activities, as many as 145 families. The sampling technique in this study was purposive sampling using Taroyamane formula calculation so that as many as 34 respondents were obtained. The measurements taken in this study were using a questionnaire while the analyzing technique was using descriptive analysis and non-parametric test analysis with Sign Test (Sign test) ) and the Wilcolxon test using the SPSS program. Based on the results of the study, it was found that the utilization of the Village Fund had an impact on the Increased Income of the Community of Sari Galuh Village, Tapung District, Kampar Regency. This is because the income of the community before the existence of village funds is less compared to the existence of village funds. so that the utilization of village funds carried out in community empowerment and village development activities increased the income of village communities by 85.29% of the total study respondents felt the increase.Keywords: Village Funds, Utilization, Impacts, Income Increase